Joseph Beuys’ Rediscovery of Man–Nature Relationship: A Pioneering Experience of Open Social Innovation - Fabio Maria Montagnino (Journal of Open Innovation: Technology, Market and Complexity, 2018)
The emerging paradigm of sustainability represents a challenging field in terms of new technologies, market regulations, and business models. Limits of both linear industrial development and consumerist way of living have been clearly identified since the late 1960s by the first systemic studies on the effect of human activities on Earth. Many contributions from different disciplines have paved the way for an open, participated, and responsible innovation approach, which is presently triggering the transition toward a nonexploitative human development. An anticipation of this conceptual framework can be found in Joseph Beuys’ art, which can still represent a source of inspiration for innovators, entrepreneurs, economists, and community leaders. In his artistic legacy—from the six blackboards of Perugia to the 7000 Oaks of Kassel—Beuys is still asking us to transform our everyday actions, joining the collective effort toward a new evolutionary stage of humanity, founded upon a holistic vision of society and nature.